Exploring the Impact of Learning Activities Supported by 360-Degree Video Technology on Language Learning, Intercultural Communicative Competence Development, and Knowledge Sharing - Shadiev, Rustam; Yu, Jiatian; Sintawati, Wayan (Frontiers in Psychology, 2021)
This study integrated intercultural learning activities into English as a foreign language (EFL) learning course in a vocational school in China. The study focused on improvement of students’ EFL abilities, intercultural communicative competence (ICC), and knowledge sharing (KS). A group of second-year students from China were partnered with a group of university students from Indonesia. 360-degree video technology was used to create an authentic and immersive intercultural learning environment in which students created content in English related to their culture and traditions, shared content with partners from the other culture, and reflected on their intercultural learning. We investigated whether learning activities supported by 360-degree video technology have positive impact on EFL learning, ICC development, and KS. The data was collected through questionnaires, tests, observations, and interviews. Three main findings were obtained in the study. The results demonstrated that 360-degree video technology-supported intercultural learning activities improved students’ EFL abilities, ICC and KS. In addition, it was found that dimensions of KS and ICC have significant relationship with each other. Finally, the students had a positive attitude toward the learning activities supported by 360-degree video technology, were satisfied with the technology, and had intentions to use it in the future for learning. On this basis, we made several suggestions for educators and researchers.